The Waiving of Parole Consideration by Inmates With Mental Illness and Recidivism Outcomes - Matejkowski, Jason (Criminal justice and behavior, 2021)
For many adults leaving prison, parole supervision can provide the support necessary for successful adjustment to community life. Those leaving prison who have a mental illness (MI) may benefit particularly from such services. However, many people who are incarcerated waive their opportunity for parole and choose instead to “max out” their sentences. This study explores whether decision-making and community risk predictors differ between people who are incarcerated with (n = 1,575) and without (n = 20,220) MI and who choose to voluntarily max out their sentence (i.e., waive parole), who max out involuntarily through denial of parole, and who are released to parole supervision. We found the presence of an MI was associated with the decision to forgo parole, but not recidivism. Those who maxed out their sentence (regardless of voluntariness of decision) had increased likelihood of recidivating. Implications for parole policy, practice, and research are discussed.